2009
DOI: 10.1002/jnr.22240
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase contributes to neurotoxicity in an excitotoxic/prooxidant model of Huntington's disease in rats: Protective role of apocynin

Abstract: Intrastriatal injection of quinolinic acid (QUIN) to rodents reproduces some biochemical, morphological, and behavioral characteristics of Huntington's disease. NAD(P)H oxidase is an enzymatic complex that catalyzes superoxide anion (O(2).(-)) production from O(2) and NADPH. The present study evaluated the role of NAD(P)H oxidase in the striatal damage induced by QUIN (240 nmol/microl) in adult male Wistar rats by means of apocynin (APO; 5 mg/kg i.p.), a specific NAD(P)H oxidase inhibitor. Rats were given APO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…Motor alterations, assessed as rotation behavior, were evaluated in animals from all experimental groups, according to previous reports [20,32]. Six days after QUIN infusion, animals were administered with apomorphine (1 mg/kg, s.c.) and separated into individual acrylic box cages.…”
Section: Circling Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Motor alterations, assessed as rotation behavior, were evaluated in animals from all experimental groups, according to previous reports [20,32]. Six days after QUIN infusion, animals were administered with apomorphine (1 mg/kg, s.c.) and separated into individual acrylic box cages.…”
Section: Circling Behaviormentioning
confidence: 99%
“…Brain tissues were collected and histologically processed according to previous descriptions [20,32]. Seven days after intrastriatally lesioned, animals from all groups were anesthetized i.p.…”
Section: Histological Examinationmentioning
confidence: 99%
“…However, increased oxidative stress is a known feature of this disease (160). Previous studies have shown increased oxidation, which was attributed to NADPH oxidase in a model of intrastriatal quinolic acid injection (115) and in vitro using the PC12 cell line overexpressing expanded polyQ proteins (17). It was not until very recently that the role of NOX2 was studied in a mouse model of HD consisting of a knock-in introducing 140 glutamine residues in the N-terminal part of endogenous Huntingtin (HD 140Q/140Q mice).…”
Section: Studies In Humansmentioning
confidence: 99%
“…Recently, we and others have linked enhanced production of reactive oxygen species (ROS) by transmembrane NADPH oxidase (NOX) enzymes to the oxidative stress and toxicity in polyQ disease [9][10][11][12]. Under normal physiological conditions NOX enzymes generate low, local levels of superoxide, thereby regulating a number of redox-sensitive intracellular signaling molecules like phosphatases, transcription factors and ion channels [8].…”
Section: Introductionmentioning
confidence: 99%